Factors Affecting The Success Of Women’s SMEs In The Digital Era: A Systematic Literature Review - Suharyati, Suharyati; Handayani, Tati (Jurnal Ekonomi, 2024)
This study conducts a systematic review of the literature on the success factors of women entrepreneurs in the digital era through bibliometric analysis and research mapping. From the 724 records identified, 86 articles were evaluated and analyzed, showing significant contributions from countries such as the United Kingdom and the United States. The methodology followed six stages of systematic review, including field mapping, comprehensive searching, quality assessment, data extraction, synthesis, and report writing. The results identified 57 main topics and generated 126 indicators grouped into ten interrelated major categories and the challenges and opportunities in female entrepreneurship. This study finds that access to finance, entrepreneurial skills, a supportive business environment, digital competence, and socio-cultural support significantly influence the success of women MSMEs. Digital transformation enables female MSMEs to reach broader markets, access alternative financing, and enhance operational efficiency and innovation.